Effect of chemical reaction on mixed convective nanofluid flow on a vertical plate with uniform heat and mass fluxes - Mondal, Hiranmoy; Goqo, Sicelo; Sibanda, Precious; De, Poulomi (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to consider a two dimensional free convective flow of a nanofluid due to the combined effects of thermal and mass diffusion in the presence of a chemical reaction of first order. The objective of the present investigation is to analyze the free convective flow in the presence of prescribed wall heat flux and mass flux condition.
Keywords: free convective flow; nanofluids; chemical reaction